The measurement of endometrial volume and sub-endometrial vascularity to replace the traditional endometrial thickness as predictors of in-vitro fertilization success. (2nd November 2019) - Maged, Ahmed M; Kamel, Ahmed M; Abu-Hamila, Fouad; Elkomy, Rasha O; Ohida, Omar A; Hassan, Sarah M; Fahmy, Radwa M; Ramadan, Wafaa
Abstract: To assess the value of endometrial thickness, volume, and sub-endometrial perfusion in women undergoing IVF. In 82 women candidate for ICSI, endometrial thickness and sub-endometrial perfusion were measured with a trans-vaginal 2 D ultrasound and 3 D power Doppler respectively on day of hCG trigger and Embryo transfer (ET). The primary outcome was the clinical pregnancy rate. Endometrial volume showing a statistically significant difference between pregnant and nonpregnant women (4.11 ± 1.19 vs. 3.4 ± 1.1 p = .019) on day of triggering and at ET (4.02 ± 1.15 vs. 3.45 ± 0.90, p = .022). VFI was significantly higher in pregnant group at both days of triggering and ET (0.54 ± 0.48 vs. 0.33 ± 0.31 and 0.47 ± 0.22 vs. 0.34 ± 0.2, p = .02). At cutoff values of 3.265 and 2.95 cm3 (70 & 80% sensitivity, specificity 64.5 & 51.6%, a positive predictive value 38.9 & 34.8%, and negative predictive value 87.0 & 88.9%) to predict pregnancy on the day of hCG trigger & ET respectively. Cutoff value for Endometrial VFI on the day of ET was 0.674 (sensitivity of 70%, specificity of 80.6%, PPV 53.8%, and NPV 89.3%). Higher endometrial volume and VFI were associated with pregnancy.